Situation Report: Czechoslovakia, 21 June 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The 14th CPCS CC Plenum: Less Carrot and More Stick / by Peter Martin Tension between Czechoslovakia and Hungary Increases / by Jan Obrman Reactions to the Events in China / by Jiri Pehe Independent Groups Call for Changes in the Legal System / by Jiri Pehe Perestroika in the Sky / by Jan Obrman Tourism: Expansion Plans Are Criticized / by Jan Obrman The Exodus of Athletes / by Jan Obrman